Mentoring the Success of Writing Scientific Articles for Yellow Stick Book Students of SMA IPA An-Nur 2 Bululawang Malang - Busthomi, Yazidul; Sundari, Sundari; Jamil, Awaludin; Aisyah, Siti; Mistar, Junaidi (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Doctoral candidates carry out duties as an integral part of the three pillars of higher education, which in its implementation cannot be separated from the other two pillars and involves the entire academic community: lecturers, students, education staff, and alums. This community service program aims to improve the quality of education in publishing articles among students of the Bululawang Malang, East Java, Yellow Book College (STIKK). The method of community service uses Participation Action Research (PAR), which is carried out using surveys, observations, practices, and counseling. The results of this service show that through the dedication of doctoral candidates, students are present in Indonesian society by carrying out student duties that not only carry out education, but also carry out research, and develop innovation, preservation, and development of superior science that is beneficial to society. Through strategies to increase the spirit of writing, including seeking inspiration from reading, reading books, articles, or literary works can be a rich source of inspiration, so that students will have many scientific works.